Aggregate tone and gross domestic product - Demers, Elizabeth; Gaertner, Fabio B.; Kausar, Asad; Li, Heather; Steele, Logan B. (Contemporary Accounting Research, 2024)
Abstract We examine whether the change in earnings announcement textual tone, aggregated across individual publicly traded firms, helps predict gross domestic product (GDP) growth. The literature finds that changes in aggregate accounting earnings do help predict GDP growth, but only when aggregate earnings changes are negative. Because conservative accounting rules limit managers' ability to communicate positive news promptly, we examine the tone of quarterly corporate earnings announcements as a possible source of timely positive information provided by firms. We find that the change in aggregate tone in the earnings announcements from the same quarter in the previous year predicts one‐quarter‐ahead GDP growth, but only when the change is positive. Our study contributes to the literature by investigating the relation between aggregate corporate disclosure tone and macroeconomic outcomes.